CHARACTERISTICS OF CELLULAR IMMUNE STATUS IN THE PATIENTS WITH CHRONIC RHINOSINUSITIS WITH NASAL POLYPS - E. L. Savlevich; S. V. Khaidukov; O. М. Kurbacheva; G. P. Bondareva; K. N. Shachnev; A. S. Simbirtsev (Медицинская иммунология)
Chronic rhinosinusitis with nasal polyps (CRSwNP) is a heterogeneous inflammatory disease of nasal cavity and paranasal sinuses characterized by inflammatory infiltration of nasal mucosa followed by damage to collagen framework, leading to tissue remodeling and polyp formation. Its pathogenetic mechanisms still remain obscure. To study appropriate trends, an evaluation of cellular immunity indices was carried out in twenty patients with the CRSwNP. Bilateral CRSwNP was clinically confirmed by endoscopic examination of nasal cavity and computed tomography scan of paranasal sinuses. In order to define the clinical phenotype of CRSwNP, allergy skin testing and a specific questioning were performed. As based on results of this study, the patients with CRSwNP were divided into following subgroups: CRSwNP + Asthma; CRSwNP + intolerance to non-steroid anti-inflammatory drugs (NSAIDs); CRSwNP + atopy. Common subpopulations of lymphocytes, such as CD3+, CD4+, CD8+, CD16+, CD19+, CD25+, CD27+, CD45+, CD45R0+, CD45RA+, CD56+ and CD127+ were detected in peripheral blood using flow cytometry techniques. Immunological data from 356 apparently healthy individuals were used as reference parameters for the control group.The study has revealed an increase in T regulatory (Treg) cells (CD4+CD25brightCD127lowtoneg), elevated absolute or relative amounts of NK cell numbers (CD3-CD16+CD56+) in parallel to sharply increased numbers of activated NKs (CD8+CD3-) in 100% of the patients, and higher absolute contents of memory B-cells (CD19+CD5-CD27+) in CRSwNP patients. When performing comparative analysis of immunologicalcharacteristics in peripheral blood between different subgroups (CRSwNP + Asthma; CRSwNP + intolerance to NSAIDs; CRSwNP+ atopy), and patients with uncomplicated CRSwNP (who didn’t have such pathology), we have proven significantly increased numbers of NKT lymphocytes (0.22±0.04), and decreased T lymphocyte activation index, i.e., a ratio of activated T helpers to memory T cells (CD4+CD45R0+) (24.4±1.72) among CRSwNP patients complicated by intolerance to NSAIDs. When comparing immunological characteristics of the patients with concomitant bronchial asthma to other subgroups, which have CRSwNP, or the patients with/without atopy, we have not detected any statistical differences for immune indexes studied (except elevation of blood eosinophils).